A multiple factor analysis of the relationship between musicality, general intelligence, and literary ability - Karlin, E (Department of Psychology, 2016)
The judgement 'that person is musical' is commonplace in our daily lives. The present writer has grown up in an intellectual environment coloured to a marked extent by interest in music and the related arts. To him it had always been a very natural phenomenon that a person should be regarded as musical or 'not-musical', and it seems justifiable to state that has attitude was but typical of his fellow-men. There appears to have prevailed for some time the idea that musicality represented some 'innate permeating spirit' which distinguished the possessor of the 'musical spark' from his brethren of more common clay. This implied that certain human beings had some general musical capacity or 'turn of mind' which was not possessed by others. Is there any justification for such an assumption? It was a question such as this which first stimulated the writer's interest towards a scientific investigation of the problem of musicality. This interest was refreshed almost continuously by a consideration of a number of further questions inevitably bound up with the consequences of the initial problem: Of the musical individuals themselves, was it true to say that their musicality was evidenced homogeneously either in degree or in quality throughout different musical operations? Was, for example, the music student who was keenest at discrimination of pitch also best at the memorizing of his music? Could anything definite be stipulated, either on a priori grounds or on the basis of experience, about the relationship existing between one's musicality and one's general intelligence? And what of the so-called allied arts; did literary ability, for instance, likewise involve a special quality, and was this ichor the same as was to explain musicality? It was as an attempt to provide a scientifically-investigated answer to such and similar questions that this analysis was originally undertaken. At the time of writing the field of the problem was entirely virgin soil; and though the writer would like to feel that this world does take an appreciable step towards clearing the obstructing growths of ignorance on the subject, yet he is obliged to point out the severely limited nature of the scope ot this thesis, owing partly to the brevity of time at his disposal and partly to the amount of wasted labour attendant upon all "pioneer" endeavour.